Public Integrity and New Rules of Conduct for Romanian MPs: A Romanian Case Study - Cynthia Carmen CURT (Transylvanian Review of Administrative Sciences, 2013)
The article refers to the problem of incompatibilities and conflicts of interests of public officials in the Romanian society and its severe consequences upon the fulfillment of the conditions of the European Commission Verification and Cooperation Mechanism’s benchmarks by Romania. The present study proposes a critical analysis of recent legislative changes of the rules of conduct for MPs in Romania, relatively to the regime of incompatibilities and conflicts of interests, emphasizing the manner in which the Parliament constantly tries to limit the prerogatives of the National Integrity Agency (NIA). Special attention is paid to the analysis of incompatibilities applicable to the MPs who are simultaneously Government members. The study follows several steps: an introduction, a critical analysis of the new legislation, focusing on the new rules of conduct for MPs, an analysis of the most important case studies and conclusions. The introduction describes the problem of incompatibilities and conflicts of interest of MPs and members of Government reflected in the recent CVM Report and the position of the National Integrity Agency. The analysis of the legislation presents a critical evaluation of the new rules of conduct for MPs, adopted in 2013 by the Romanian Parliament; then, analyzing the most important and recent case studies, general patterns in the field of procedures of incompatibilities and conflicts of interests emerge. Conclusions propose legislative solutions in terms of raising the standards of public integrity.